ASSISTANCE IN ENGLISH LANGUAGE LEARNING FOR STUDENTS OF MI AL-MAARIF SIDODADI - Husein, Ach Munawi; Agustin, Danie (International Journal of Community Service in Language, Literature, Culture, and Their Teaching, 2026)
English language learning assistance is one of the strategic efforts to improve the basic English language skills of madrasah ibtidaiyah students. This community service activity aims to improve students' understanding of basic vocabulary, pronunciation skills, and interest in learning English at MI Al-Ma'arif Sidodadi. The methods used in this activity include a participatory approach through direct tutoring, the use of interactive learning media such as flashcards, songs, educational games, and simple conversation exercises. The activity was carried out in several stages, namely planning, implementation of mentoring, and evaluation of student learning outcomes. The results of the mentoring showed an increase in vocabulary mastery, students' courage in pronouncing simple words and sentences, and increased student enthusiasm during the learning process. In addition, varied and enjoyable learning methods proved to be able to create a conducive and interactive learning atmosphere. Thus, this English learning mentoring activity made a positive contribution in supporting the improvement of English learning quality at MI Al-Ma'arif Sidodadi and can be used as an applicable mentoring model for other elementary schools.